Characterization and dissolution studies of Furosemide solid dispersions using polyethylene glycol (PEG), talc and PEG-talc as dispersion carriers - Yandi Syukri; Diny Rizayulianty; Yuni Darty (Indonesian Journal of Pharmacy, 2004)
Solid dispersions of furosemide were prepared by melting and solvent methods using polyethylene glycol (PEG) 6000, talc and PEG – talc as dispersion carrier in order to improve furosemide dissolution. The increase of dissolution and physical properties of its powder was evaluated. Only furosemide solid dispersions with combination of PEG – talc 1 : 3 showed a good physical properties. The assay of the effect of PEG – talc ratio on furosemide dissolution showed that the increase of ratio of PEG – talc increased significantly dissolution rate.Key Word : furosemide, solid dispersion, dissolution